Mood and Modality in the song “Reckless” by Madison Beer within Semantics - Rotua Sinta Marito Pakpahan; Bernieke Anggita Ristia Damanik (JURNAL ILMIAH NUSANTARA, 2026)
Mood and modality are important aspects of semantic studies because they express attitudes, emotions, certainty, obligation, and intention through language. The aims of this research are to identify and describe the types of mood and modality found in the song "Reckless" by Madison Beer and to explain their semantic meanings. This research uses a qualitative descriptive method with semantic analysis as the main approach. The data source is the lyrics of the song "Reckless." This study analyzed clauses and modal expressions based on Halliday's theory of mood and Palmer's theory of modality. The findings show that the declarative mood is the dominant mood used in the song because the lyrics mainly express emotional experiences and reflections. In addition, three types of modality were identified, namely epistemic modality, deontic modality, and dynamic modality. Dynamic modality appears most dominantly because the song strongly expresses emotional ability, willingness, regret, and vulnerability. The use of mood and modality in the lyrics strengthens the emotional meaning of heartbreak, disappointment, betrayal, and sadness conveyed by the singer. It is expected that this research can provide a deeper understanding of how mood and modality function in expressing emotions through song lyrics and contribute as a reference for future studies in semantics, especially those analyzing mood and modality in literary works such as songs, poems, or other lyrical texts.